Emotional intelligence, empathy and alexithymia: a cross-sectional survey on emotional competence in a group of nursing students: Emotional competence in nursing students - Di Lorenzo, Rosaria; Venturelli, Giulia; Spiga, Giulia; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2019)
Background: Emotional intelligence (EI) is the ability to recognize and manage one’s own and others’ emotions, empathy is the ability to understand how others feel, whereas alexithymia represents the difficulty in feeling and verbally expressing emotions.  Emotional competences are important requirements for positive outcomes in nursing profession. The aim of the study: To analyze EI, empathy and alexithymia in nursing students. Methods: We conducted a cross-sectional survey in a sample of 237 students (53 males, 184 females), attending both the 1st and 3rd year of the University Nursing Course in Modena. We administered three Italian validated scales: Schutte Self-Report Emotional Intelligence Test (SSEIT), Jefferson Scale of Empathy - Health Professions Student (JSE-HPS), Toronto Alexithymia Scale (TAS-20). Data were statistically analyzed. Results: Statistically significant differences were found between the 1st and 3rd year students at SSEIT (t=-0.6, p=0.52), JSE-HPS (t=-3.2, p=0.0016) and TAS-20 scores (t=-3.54, p=0.0005). Among 3rd year students, females obtained significantly different scores from those of males at SSEIT (t=2.8, p=0.006). All three scales reported a Cronbach’s alpha >0.80. SSEIT correlated positively with JSE-HPS (Spearman’s rho=0.15, p=0.02) and negatively with TAS-20 (Spearman’s rho=-0.18, p=0.006). Conclusions: Our study highlighted a good level of emotional skills among students at the beginning of nursing training, further increased by the last year of the course, suggesting that emotional competences can be learned, and confirmed that empathy, but not alexithymia, is a dimension of EI.